Predicting animal abundance through local ecological knowledge: An internal validation using consensus analysis ... : التنبؤ بوفرة الحيوانات من خلال المعرفة البيئية المحلية: التحقق الداخلي باستخدام تحليل الإجماع ... - Franciany Braga‐Pereira; Pedro Mayor; Thaís Q. Morcatty; Pedro E. Pérez‐Peña; Mark Bowler; Marina Albuquerque Regina de Mattos Vieira; Rômulo Romeu Nóbrega Alves; John E. Fa; Carlos A. Peres; Aldaléa Sprada Tavares; Carla Mere‐Roncal; Carlos González‐Crespo; et al. (OpenAlex, 2024)
Abstract Given the ongoing environmental degradation from local to global scales, it is fundamental to develop more efficient means of gathering data on species and ecosystems. Local ecological knowledge, in which local communities can consistently provide information on the status of animal species over time, has been shown to be effective. Several studies demonstrate that data gathered using local ecological knowledge (LEK)‐based methods are comparable with data obtained from conventional methods (such as line transects and camera traps). Here, we employ a consensus analysis to validate and evaluate the accuracy of interview data on LEK. Additionally, we investigate the influence of social and bioecological variables on enhancing data quality. We interviewed 323 persons in 19 villages in the Western and Central Amazon to determine the level of consensus on the abundance of hunted and non‐hunted forest species. These villages varied in size, socio‐economic characteristics and in the experience with wildlife ... : بالنظر إلى التدهور البيئي المستمر من المستويات المحلية إلى العالمية، من الضروري تطوير وسائل أكثر كفاءة لجمع البيانات عن الأنواع والنظم الإيكولوجية. وقد ثبت أن المعرفة البيئية المحلية، التي يمكن للمجتمعات المحلية أن تقدم فيها باستمرار معلومات عن حالة الأنواع الحيوانية مع مرور الوقت، فعالة. تُظهر العديد من الدراسات أن البيانات التي تم جمعها باستخدام الأساليب القائمة على المعرفة البيئية المحلية (LEK) قابلة للمقارنة مع البيانات التي تم الحصول عليها من الطرق التقليدية (مثل مقاطع الخطوط ومصائد الكاميرا). هنا، نستخدم تحليل الإجماع للتحقق من صحة وتقييم دقة بيانات المقابلة على LEK. بالإضافة إلى ذلك، نقوم بالتحقيق في تأثير المتغيرات الاجتماعية والبيولوجية على تحسين جودة البيانات. أجرينا مقابلات مع 323 شخصًا في 19 قرية في غرب ووسط الأمازون لتحديد مستوى الإجماع على وفرة أنواع الغابات التي يتم اصطيادها وغير التي يتم اصطيادها. اختلفت هذه القرى في الحجم والخصائص الاجتماعية والاقتصادية وفي تجربة الحياة البرية لسكانها. قدر الأشخاص الذين تمت مقابلتهم الوفرة النسبية لـ 101 نوع مع مجموعة واسعة من الخصائص البيئية الحيوية ...